About physical parameters of experimental reactor- stellarator in the conditions of ambipolarity of neoclassical transport fluxes - Rudakov, V.A. (Вопросы атомной науки и техники, 2012)
Parameters of an experimental stellarator reactor operating under conditions of ambipolarity of neoclassical transport fluxes are calculated with the use of a space-time numerical code. Dimensions of the system and the confinement magnetic field are taken the same as in the ITER tokamak reactor. The paper shows a possibility of engineering development of an experimental stellarator reactor with parameters comparable to these of an experimental tokamak reactor. C использованием пространственно-временного численного кода рассчитаны параметры экспериментального реактора-стелларатора в условиях амбиполярности неоклассических транспортных потоков. Размеры системы и удерживающее магнитное поле приняты такими же, как и в реакторе-токамаке ITER. Показана возможность создания экспериментального реактора-стелларатора с характеристиками, сопоставимыми с характеристиками экспериментального реактора-токамака. З використанням просторово-часового чисельного коду розраховано параметри експериментального реактора-стеларатора в умовах амбіполярності неокласичних транспортних потоків. Розміри системи і утримуюче магнітне поле прийняті такими ж, як і в реакторі-токамаці ITER. Показана можливість створення експериментального реактора-стеларатора з характеристиками, порівнянними з характеристиками експериментального реактора-токамака.